Interaction of TFSI-Imidazole and TFSI-Pyridinium ILs with MOFs from Molecular Docking Simulation - Abdullah, N.A.F. (Springer Science and Business Media B.V., 2021)
Metal Organic Frameworks (MOFs) are porous material consisting of coordination bonds between metal cations and organic bridging ligands. Owing to its large surface area and tunable porosity, MOFs are an ideal material for various applications. The consolidation of ionic liquids (ILs) interior MOF might enhance the performance of pristine MOF, however, the depth study of fundamental interaction between IL and MOF are scarce. The interactions between the MOFs and ILs moiety, especially the types of interaction play an important role in determining the stability, compatibility, and selectivity of this hybrid material. This research will be centered on differing qualities of MOF-IL by utilizing computational approach to study the interaction of ILs and MOFs. Molecular docking calculation was carried out to identify the binding energy (ÎGbind) between MOF5, ZIF8, UIO66 with TFSI-imidazole (EMIM, PMIM, BMIM) and TFSI-pyridinium ILs (BPYDM, EMPYDM, PMPYDM, BMPYDM). The initial 3D structures were retrieved from website database and were prepared using default parameters in docking software. The ILs was docked consecutively into the MOFs cavity inside the grid box dimension to identify binding sites of MOF. From the results, TFSI-imidazole and TFSI-pyridinium ILs exhibited good interaction with MOFs. In term of highest stability and strongest binding affinity, the PMPYDM-TFSI showed superior binding towards UIO66 with ÎGbind of â8.60Â kcalÂ molâ1. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.